ATP/ADP biosensor organoids for drug nephrotoxicity assessment - Susa, Koichiro; Kobayashi, Kenichi; Galichon, Pierre; Matsumoto, Takuya; Tamura, Akitoshi; Hiratsuka, Ken; Gupta, Navin R.; Yazdi, Iman K.; Bonventre, Joseph V.; Morizane, Ryuji (Frontiers in Cell and Developmental Biology, 2023)
Drug nephrotoxicity is a common healthcare problem in hospitalized patients and a major limitation during drug development. Multi-segmented kidney organoids derived from human pluripotent stem cells may complement traditional cell culture and animal experiments for nephrotoxicity assessment. Here we evaluate the capability of kidney organoids to investigate drug toxicity in vitro. Kidney organoids express renal drug transporters of OAT1, OAT3, and OCT2, while a human proximal tubular cell line shows the absence of OAT1 and OAT3. Tenofovir and aristolochic acid (AA) induce proximal tubular injury in organoids which is ameliorated by an OAT inhibitor, probenecid, without damage to podocytes,. Similarly, cisplatin causes proximal tubular damage that can be relieved by an OCT inhibitor, cimetidine, collectively suggesting the presence of functional OATs and OCTs in organoid proximal tubules. Puromycin aminonucleoside (PAN) induced segment-specific injury in glomerular podocytes in kidney organoids in the absence of tubular injury. Reporter organoids were generated with an ATP/ADP biosensor, which may be applicable to high-throughput screening in the future. In conclusion, the kidney organoid is a useful tool for toxicity assessment in the multicellular context and may contribute to nephrotoxicity assessment during drug development.